Konsep Ideal Pendidikan Islam sebagai Relasi Primordial Manusia dengan Tuhan - Mahfud, Mahfud (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2017)
Education is an urgent thing for human life. For that education has a primary position in human life. But in the context of education is perceived as a tool to gain wealth and power. His soul and heart were filled with worldly hopes. The existence of existing education no longer leads man to discover who his Lord is, but directed at the gods that are material (new idols). Therefore, Islamic education should be understood as one of the right concepts to restore human relations with God. The concept of Islamic education is an appropriate means to restore humans to their primordial relation with God. The concept of Islamic education in line with national education as set forth in the 1945 Constitution and the National Education System Law no. 20 year 2003. Is an education system that comes from a single paradigm that is the concept of Oneness of God. Islamic education introduces "Tauhid", the philosophy of the state also embraces the concept of monotheism in the first principle of Belief in the One Supreme. From this single paradigm can then be drawn the conclusion that Islamic education is the only concept of education that can restore man to God.